2001
DOI: 10.1203/00006450-200112000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Hypocapnia and Other Ventilation-Related Risk Factors for Cerebral Palsy in Low Birth Weight Infants

Abstract: Ventilatory management patterns in very low birth weight newborns, particularly iatrogenic hypocapnia, have occasionally been implicated in perinatal brain damage. However, such relationships have not been explored in large representative populations. To examine the risk of disabling cerebral palsy in mechanically ventilated very low birth weight infants in relation to hypocapnia and other ventilation-related variables, we conducted a population-based prospective cohort study of 1105 newborns with birth weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(109 citation statements)
references
References 37 publications
2
105
1
1
Order By: Relevance
“…[30][31][32][33] It must be recollected that, as a group, our CDH participants had abnormally high pH and abnormally low CO 2 , both pre-and post-operatively (see Table 2). The CDH survivors who showed the best intellectual and motor outcomes were those whose pH and CO 2 levels were closest to the normal range.…”
Section: Discussionmentioning
confidence: 90%
“…[30][31][32][33] It must be recollected that, as a group, our CDH participants had abnormally high pH and abnormally low CO 2 , both pre-and post-operatively (see Table 2). The CDH survivors who showed the best intellectual and motor outcomes were those whose pH and CO 2 levels were closest to the normal range.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have demonstrated that a change in clinical practice to avoid hyperoxia is associated with significant decrease in neonatal morbidity but does not have a detrimental effect on developmental outcome at 18 months (Deulofeut et al, 2006). Moreover, another study identified hyperoxia as one clinical risk factor for abnormal neurologic outcome of preterm infants (Collins et al, 2001). This finding is consistent with the observation that the duration of oxygen therapy in premature infants was predictive of the cognitive outcome at 8 years (Short et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperoxia has been implicated in the pathogenesis of bronchopulmonary dysplasia and retinopathy of prematurity (Saugstad, 2001;Chow et al, 2003). There is increasing evidence that hyperoxia may negatively influence brain maturation and development (Collins et al, 2001;Felderhoff-Mueser et al, 2004;Klinger et al, 2005;Gerstner et al, 2006). However, the mechanism of hyperoxia-induced injury and the identification of vulnerable cells in the human brain are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Always wean the FiO 2 (slowly) when SpO 2 is >95% in a preterm infant breathing supplemental oxygen. If saturation remains at >95% in room air (FiO 2 0.21), this is an indication the infant did not need supplemental oxygen ventilated 50 and was also found to increase adverse outcomes, including CP, after perinatal hypoxia-ischemia encephalopathy in term newborns. 51 The better long-term neurodevelopmental scores in preterm infants managed with practices to prevent hyperoxia 40 concur with these findings.…”
Section: Tension Of Arterial Oxygen (Pao 2 )mentioning
confidence: 99%